Wireless Real-Time Data Acquisition System for Aerodynamic Characterization of a Wind Turbine - Casallas, Jhoan S.; Parra-Peñuela, Hector Guillermo; Gaona, Elvis E. (Ingeniería, 2023)
Context: Wind energy sources utilize renewable, free, and environmentally friendly resources, so there are projects focused on the design of wind turbines to increase their efficiency. Simulations using computational fluid dynamics techniques allow designs to be analyzed. which, are then validated through experimentation and wind tunnel measurements. Method: Data acquisition is performed by using Wind Sensor Rev.P sensors to measure wind velocity, and MMA7361 accelerometer to measure the vibrations generated by the wind in the turbine. Additionally, an ESP32 is required to process and transmit the data via Bluetooth, thus facilitating the installation of the real-time monitoring module inside the wind tunnel. Results: A monitoring module with a sampling rate of 5 ms was obtained, thus allowing real-time data acquisition, with a resolution of 12 bits for good data capturing accuracy and a transmission rate of approximately 74000 bps. An application capable of plotting 3D acceleration and 2D wind speed signals was also created. Conclusions: The device developed serves as a support for future wind turbine design projects since it is wireless, its installation is simple, it facilitates data collection inside a wind tunnel, and it allows visualizing the turbine’s behavior in real time by means of a graphic interface.